Lebanese community-based pharmacists' interest, practice, knowledge, and barriers towards pharmacy practice research: A cross-sectional study - Rouba Karen Zeidan; Souheil Hallit; Rony M. Zeenny; Pascale Salameh (Elsevier, 2019)
Objective: To assess the interest, knowledge, practice and barriers of Lebanese community-based pharmacists towards research, and to examine factors associated with interest. Methods: A cross-sectional survey, conducted between January and May 2017, enrolled community pharmacists using a proportionate random sample of community pharmacies in the five districts of Lebanon, using the list of pharmacies provided by the Lebanese Order of Pharmacists. In the absence of validated questionnaires to answer our objectives, we created a questionnaire based on previous research. The questionnaire was modified based on the experiences and issues raised during focus groups with research active pharmacists and research oriented community pharmacists. Results: A total of 399 pharmacists was enrolled. The results showed that 231 (72%) were conscious about the important role of research in the community pharmacy setting whereas only 5.6% considered it not important. Over two-thirds (68.5%) of the pharmacists declared being interested in participating in research. There was a statistical difference in the percentage of correct answers between auto-declared and corrected responses for all terms, with all p < 0.001.The most reported barrier was lack of time during hours of work (90.9%), followed by the lack of pharmacy staff (73.7%), lack of financial resources (68.9%), patient's lack of education and resistance to participation (64.8%), and lack of support (63.8%). Age (aOR = 0.92), years of experience (aOR = 1.06), and having been involved in research (aOR = 3.17) were associated with higher interest in research. Having studied in Lebanon (aOR = 3.63), having received previous research courses (aOR = 11.12) and being interested in research (aOR = 2.74) were associated with having participated in research projects during their professional experience. Conclusion: Lebanese pharmacists have the good will to conduct and participate in research, but are lacking knowledge; this issue needs to be addressed vividly. Addressing the identified barriers could improve the research output of Lebanese community pharmacists. Keywords: Barriers, Community pharmacist, Interest, Knowledge, Research